The Influence of Warehouse Operational Performance on the Acceleration of Goods Delivery at PT. Satria Antaran Prima Tbk Padang Branch - Syifa Tanjung, Lailatul; Kumala Sari, Resy; Yusmita, Yesi; Syahrin Hasibuan, Alfi; Aliza, Nur (Journal of Engineering Science and Technology Management, 2024)
This research aims to analyze the influence of warehouse operational performance on the acceleration of goods delivery at PT. Satria Antaran Prima Tbk Padang Branch. Optimal warehouse operational performance is one of the key factors in supporting supply chain effectiveness, especially in speeding up the delivery of goods to consumers. The research method used is a descriptive method with data collection through sources in the warehouse and logistics department. The data obtained was analyzed using descriptive methods to test warehouse operational processes regarding the speed of delivery of goods. The research results show that there is a significant influence between warehouse operational performance and the acceleration of goods delivery. This means that improvements in storage processes, inventory management, and distribution arrangements in warehouses can directly increase the speed of delivery of goods to consumers. Therefore, PT. Satria Antaran Prima Tbk is advised to continue evaluating and improving warehouse operational performance as part of a strategy to increase customer satisfaction.